If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + (x + 3) = 75 Reorder the terms: 2x + (3 + x) = 75 Remove parenthesis around (3 + x) 2x + 3 + x = 75 Reorder the terms: 3 + 2x + x = 75 Combine like terms: 2x + x = 3x 3 + 3x = 75 Solving 3 + 3x = 75 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 3x = 75 + -3 Combine like terms: 3 + -3 = 0 0 + 3x = 75 + -3 3x = 75 + -3 Combine like terms: 75 + -3 = 72 3x = 72 Divide each side by '3'. x = 24 Simplifying x = 24
| 7p+26=-32p+-40+6p | | 5(2z+6)=-4(-5-2z)+3z | | z-3z=8z-7-z | | x=8pi-pi | | 5(x+2)=4x-8 | | 5(2n+12)=4n | | 150n-50=n+325 | | 2(-5x+5)=-4x+4 | | [5a^2-20a+20]+[3a+3]=25 | | -84=2(6+8a) | | x+3=(x-3)(x-3) | | 3a-45b*j=2 | | 5x+30=11x+48 | | w+(3+w)=25 | | z-3z=8z-7-2 | | 150n-50=100+325 | | 7x^2+12=25x | | -67+6x=-6(-x+7)-4 | | 4x^2-6x=4x^2-3x-27 | | 7x+10=6x+3 | | -9y^2-6y^2+y^2= | | 7(4y-6)=14 | | 4x-3(0)=17 | | -120x=-60 | | -6g=-30 | | 9=X*44 | | -5(4t-4)+6t=8t-9 | | c+(5+c)=33 | | 8-4(2+l)= | | q-21=-7 | | 0=4(0)+7 | | -2(1-4x)+2x=-82 |